Efficacy of scorpion antivenom plus prazosin compared with prazosin alone for scorpion sting in children: A cross sectional study - R. Nagarjun; Pooja G. Manoli; A. Ashoka (Al Ameen Medical College, 2024)
Background: Scorpion sting can pose as a life threatening acute medical emergency, which, if not attended to on an emergency basis can result in mortality. Scorpion venoms are a composed of a complex mixture of proteins. There has been documentary evidence that scorpion antivenom and prazosin, an alpha blocker are very effective in reducing the mortality rate following scorpion bite. Aim: To compare the time required for complete resolution of the autonomic manifestations associated with prazosin alone and prazosin with antiscorpion venom in children with scorpion sting envenomation. Methods: This was a cohort study including 44 children less than 18 years of age, presenting to the paediatric emergency or outpatient department with scorpion sting within 10 hours of sting from the 2 hospitals attached to J.J.M Medical College, Bapuji Child Heath Institute and C.G Hospital from November 2019 to November 2021. Results: The mean age was 10.35 ± 3.76 in the prazosin + antivenom group and in the prazosin group was 11.58±3.87 years. Males were commonly affected. In the present study, overall, 14 cases (16.67%) presented within 4 hours of bite and 30 (83.3%) cases after 4 hours of bite. The clinical features seen in the prazosin alone group and prazosin + anti venom group was cold extremities, excessive sweating, CNS effects and cardiac involvement. 58.33% had evidence of grade 3 envenomation. The days of hospitalization was 5.39 days +2 .72 days in the group prazosin + antivenom and in the group prazosin alone it was 9.27+ 4.57 days. Higher doses of prazosin were used in those who received prazosin alone ,mean was 8.50 SD +1. 89 and in group prazosin +antivenom, the mean was 6.00SD +2.11. Higher post medication cardiac dysfunction was seen in prazosin + antivenom, i.e 27.27% and the group prazosin alone it was 9.09%. Conclusion: As compared to prazosin alone the combination of prazosin with antivenom is very effective by reducing the time to alleviate the autonomic over activity.